Fixed Point Results for Single and Multivalued Maps on Partial Extended b-Metric Spaces - Hassen Aydi; Samina Batul; Muhammad Aslam; Dur-e-Shehwar Sagheer; Eskandar Ameer (Journal of Function Spaces)
This article is based on the concept of partial extended b-metric spaces, which is inspired by the notions of new extended b-metric spaces and partial metric spaces. Fixed point results for single and multivalued mappings on such spaces are also presented. Few examples are also provided to elaborate the concepts.